Pengaruh AUKUS terhadap Stabilitas Indo-Pasifik dan Sikap Indonesia [The Influence of AUKUS to Indo-Pacific Regional Stability and Indonesia’s Stance] - Nindya, Annisa Putri; Abiyya, Rifqy Alief (Jurnal Politica, 2022)
In the midst of heating up tensions in the vortex of the South China Sea dispute, AUKUS emerged as a new alliance under a trilateral agreement that was accused of being a security pact. Some observers argue that the alliance consisting of Australia, Britain and America is a new maneuver for their bloc to fight the increasingly aggressive domination of the People’s Republic of China (PRC) in the Indo-Pacific region. With the AUKUS mission to maintain the stability of the security of the Indo-Pacific, the imagined possibility is the opposite and becomes the background for the reactions of various countries in the region, one of which is Indonesia. Indonesia is one country that has expressed concern about an arms race that may be unavoidable. Moreover, Indonesia is also seen as a middle power that has an important role in responding to tensions between the two camps. Therefore, this paper will analyze the emergence of AUKUS for the Indo-Pacific and Indonesia’s position including the direction of its foreign policy related to the existing issues. The topics are analyzed using Regional Security Complex Theory and Offense-Defense Theory and qualitative descriptive methods. After further elaboration, it can be seen that the geopolitical dynamics of the Indo-Pacific are indeed constantly creating tension due to competition from external parties. Indonesia as a non-aligned country and adherents of free and active politics is expected to be able to reinterpret its principles and be firm in pioneering collective security with a firm voice with other ASEAN countries.AbstrakDitengah memanasnya tensi dalam pusaran konflik sengketa Laut Tiongkok Selatan, AUKUS muncul sebagai aliansi baru di bawah kesepakatan trilateral yang dituding sebagai pakta keamanan. Beberapa pengamat berpendapat bahwa aliansi yang terdiri dari Australia, Inggris dan Amerika tersebut adalah manuver baru bagi blok mereka untuk melawan dominasi Republik Rakyat Tiongkok (RRT) yang semakin agresif di kawasan Indo-Pasifik. Dengan misi AUKUS untuk menjaga stabilitas keamanan Indo-Pasifik, kemungkinan yang dibayangkan terjadi justru sebaliknya dan menjadi latar belakang dari reaksi beragam negara-negara dalam kawasan salah satunya adalah Indonesia. Indonesia adalah salah satu negara yang menyatakan kekhawatirannya terhadap perlombaan senjata yang mungkin tidak dapat terhindarkan. Oleh karena itu, tulisan ini akan memaparkan secara analisis dari munculnya AUKUS bagi Indo-Pasifik serta posisi Indonesia mencakup arah kebijakan luar negerinya berkaitan dengan isu yang ada. Topik dalam tulisan ini dianalisis menggunakan Regional Security Complex Theory dan Offense-Defense Theory dan metode kualitatif dengan pendekatan deskriptif. Setelah elaborasi lebih lanjut, dapat diketahui bahwa dinamika geopolitik Indo-Pasifik memang terus-menerus menciptakan tensi akibat persaingan pihakpihak eksternal. Indonesia sebagai negara non-blok dan penganut politik bebas aktif diharapkan mampu memaknai kembali prinsipnya dan tegas dalam mempelopori keamanan kolektif dengan sikap tegas satu suara bersama negara ASEAN lainnya.